Pengembangan Media Pembelajaran Video Animasi 2 Dimensi Berbasis Computing dan Slideshow Materi Cerita Rakyat Semarangan - Sholahunnisa, Awalia; Insani, Nur Hanifah (Piwulang Jurnal Pendidikan Bahasa Jawa, 2024)
The impact of globalization has reduced students' appreciation of local culture, including folklores. Students' knowledge of folklore that developed in Semarang is still minimal so teachers need to apply suitable learning methods and media. The solution to the problem is to develop learning media in the form of animated videos of Semarangan folklore material. This research uses the method of Research and Development or development research. The data from this study were obtained from the needs analysis, namely teachers and students of SMP Negeri 12 Semarang using an instrument in the form of a questionnaire, and the results of validation tests from material experts and , media experts. The result of this research is that students and teachers need learning media in the form of animated audiovisual media. The prototype of animated media was designed based on the needs analysis of students and teachers. The selection of fonts, colors is adjusted to the interests of teachers and students, namely the selection of fonts, and a combination of bright colors. Based on the validation test results from material and media experts, the media that has been designed is included in the category that is very feasible as a learning media.